PENGEMBANGAN MEDIA PEMBELAJARAN SPASI (SISTEM PENCERNAAN SAPI) PADA MATERI IPA TEMA MAKANAN SEHAT SISWA KELAS V SD N TEGALOMBO 04 - Kristianto, Heru; Fajriyah, Khusnul; Sukamto, Sukamto (Universitas Sarjanawiyata Tamansiswa, 2021)
This research is based on the lack of media used in learning and the absence of model-based learning media as a supporting medium of learning. This research aims to develop and know the validity and practicality of space learning media (Cow Digestive System) in grade V elementary school. The research method used is the development method or Research and Development (R&D). The subjects of this study were students of grade V of SD Tegalombo State 04 and SD Negeri Tegalombo 03. The results showed that the average media validation poll resulted in 97.5%, material validation questionnaire by 80%, teacher response questionnaire by 96%, and teacher response questionnaire of 94.85%.